Effect of a probiotic on prevention of salmonellosis in pigs - Beeman, K.B.; Erickson, D.E.; Henning, B.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine if a commercial probiotic compound could be used to bring about competitive exclusion of Salmonella organisms. The probiotic material was added to the feed of one group of pigs and was not added to the feed of a control group. Both groups of pigs were dosed orally with 10^6 CFU of Salmonella cholerasuis. All pigs were affected; however, the treated group demonstrated less illness than the control group.
Keywords: Swine; Probiotic; Salmonellosis; Competitive exclusion